Development of Lecturer Performance Evaluation Tools in the Implementation of Merdeka Belajar Kampus Merdeka - Nurjaman, Maman; Sa’ud, Udin Syaefudin; Prihatin, Eka; Herawan, Endang (Universitas Islam Negeri Raden Intan Lampung, 2023)
This research aims to develop a model for assessing lecturer performance that includes tools, evaluation standards, standard-setting, computer programs, assessment standards, and instructions for using evaluation results. This is a development project. Nine experts approved the instrument design before using Aiken's V formula to determine content validity, exploratory factor analysis to determine construction validity, and Cronbach's alpha to determine reliability. The study's findings revealed that: 1) the entire instrument meets the criteria for validity; 2) an instrumental analysis of the teacher's instructional activities revealed reliability of the preparation, implementation, and evaluation components of 0.843; and finally, 3) the effectiveness of teaching, the efficacy of research, the efficacy of dedication to the community, and the qualifications of lecturers were all taken into account when evaluating the efficiency of the lecturer's employment.